BAHASA INDONESIA MEMAINKAN PERANAN PENTING DALAM KEMAMPUAN MENDENGAR SISWA - Elmiwati; Rismiwati (STAI Miftahul Ulum Tanjungpinang, 2024)
In teaching- learning process, media used to accelerate the communication is called the Educational media. Learning using audio visual myriad benefits, due to the use of audio visual can gain more experience, impressive, more clearly and concrete. The aim of this research was to know the effectiveness of audio visual media on students’ listening ability at the morning class of first semester of Engeenering Faculty, Maritim Raja Ali Haji University? researcher used experimental research. Based on the data analysis and the result, the researcher concluded that using of audio-visual media was effective in teaching listening because there was an increasing in the number of students who have good grades. Before giving audio-visual media was only one student (4%) and after being given the audio-visual media to 14 students (50%). It means that, there was a positive effect of using audio-visual media in increasing students’ listening ability.